Cessante ratione legis, cessat ipsa lex? Data and privacy protection in the digitized energy sector amidst green and digital transformation processes - Zoran Dimović (Cogent Social Sciences, 2024)
The ex ante regulation of green and digital transformation processes is set to significantly impact personal data and privacy protection in the digitalized energy sector. Although the drive for digitization aligns with EU values, goals, and objectives, it does not inherently ensure compliance with fundamental human rights. While general rules for personal data and privacy protection are sufficiently flexible to allow for appropriate interpretation, implementing sector-specific human rights regulations would enhance legal certainty. This is particularly crucial given the heightened sensitivity of the electricity sector compared to natural gas or heat. The observed lack of standardization in the digitalization of the energy sector is likely to become even more pronounced with the continued development of digital technologies. This increasing complexity underscores the need for comprehensive regulatory frameworks that address both the opportunities and challenges presented by the green and digital transformation. These considerations have significant implications for policymakers, academics, and legal practitioners. Understanding and addressing these issues is essential for ensuring that the transformation processes in the energy sector are conducted in a manner that respects personal data and privacy protection while advancing sustainable and digital innovation. The development of robust and specific regulations will be key to balancing these objectives and ensuring the protection of fundamental human rights in an increasingly digitalized energy landscape.